Une collecte de complaintes criminelles en Occitanie - Xavier Vidal (Criminocorpus)
This article presents the results of a field survey carried out in the Occitan region in France. The research has been focused on the work of folk song writers. The results show us that, at least for a more recent period, an important place was given to the French language in the allover production of those songwriters. The criminal laments do not escape from this rule. The valorization of French as the language of religion and morality appears in Protestantism. This religion irrigates the history of the Occitan region. In comparison to the moralist spirit of the French, the Occitan language of everyday life appears to be more suitable to describe moments of transgression and drunkenness for example during carnivals and charivaris.